Creatinine-to-cystatin C ratio as muscle assessment tool and predictive value for mortality and sarcopenia in patients with chronic kidney disease: a meta-analysis - Zheng, Wen-He; Hu, Yan-Ge; Yu, Da-Xing; Huang, Hui-Bin (Frontiers in Nutrition, 2025)
BackgroundThe creatinine-to-cystatin C ratio (CCR) has been developed as a novel biomarker of sarcopenia and prognostic evaluation in various hospitalized populations. However, evidence supporting the use of CCR in patients with chronic kidney disease (CKD) remains limited. Thus, we aimed to evaluate whether CCR could be a marker of muscle mass for predicting prognosis in patients with CKD.MethodsWe searched PubMed, Embase, Wanfang, China National Knowledge Infrastructure, Web of Science, and Cochrane Library databases up to March 15, 2025. Studies were included if they reported a relationship between CCR and muscle measurements or prognosis in adults with CKD. The risk of bias in non-randomized studies-of exposures tool was used to assess the quality of the study. The primary outcome was all-cause mortality. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines.ResultsNine studies (seven cohort and two cross-sectional studies) involving 31,673 adults were included. The quality of the included studies ranged from moderate to high. Pooling the results from multifactorial analyses showed that CCR can reliably predict mortality, either using CCR as a category variable [n = 24,778; hazard ratio (HR) = 2.16; 95% CI, 1.40–2.88; I2 = 48%] or a continuous variable (n = 3,313; HR = 0.73; 95% CI, 0.57–0.93; I2 = 68%). CCR was positively correlated with handgrip strength (n = 874; r = 0.38, P < 0.001) and skeletal muscle index (n = 357; r = 0.42, P < 0.001). Similarly, the area under curves (AUC) suggested that CCR had poor-to-fair diagnostic efficacy for handgrip strength (AUC = 0.640; 95% CI: 0.605–0.0.675), skeletal muscle index (AUC = 0.684; 95% CI: 0.596–0.772), and sarcopenia (AUC = 0.720; 95% CI: 0.619–0.822). For nutrition status, lower CCR was associated with significantly lower albumin but not body mass index.ConclusionsThis meta-analysis suggests that CCR could serve as a valuable tool for evaluating muscle mass, as well as an indicator of nutritional status and an independent predictor of prognosis in patients with CKD. These findings encourage the use of CCR in this patient population. However, more high-quality studies are needed to confirm these findings.Systematic review registrationhttps://inplasy.com/inplasy-2022-9-0097/, identifier: NPLASY202290097.